Robust topological valley-locked waveguide transport in photonic heterostructures - Qiankun Zhang; Xiaohua Xing; Die Zou; Yin Liu; Bingxuan Mao; Guizhong Zhang; Jianquan Yao; Chunmei Ouyang; Liang Wu (Results in Physics, 2023)
Topological valley-locked edge state has arisen a rapidly developing research topic in photonics for its gapless dispersion and immunity against intervalley scattering. However, valley-locked edge state is usually confined around the domain walls of valley photonic crystals (VPhCs) with different topological invariants, which decreases the flexibility of valley photonic devices and limits its application in on-chip integration. Here we propose a topological valley-locked waveguide (TVLW) with a width degree of freedom (DOF) by using a photonic heterostructure where a VPhC characterized by Dirac cones is sandwiched by two VPhCs with opposite valley Chern numbers. The TVLW is available for the transmission of waveguide states which maintain the properties of momentum-valley locking and robustness to defects. Taking advantage of these properties of TVLWs, we design a topological energy concentrator for field enhancement and a topological power splitter with an arbitrary splitting ratio by introducing the rotation angle of channels as a new DOF. Compared with conventional waveguides, the proposed TVLWs with tunable mode-width are more flexible to interface with the existing photonic devices, which provide broad application prospects in on-chip communication and photonic integrated networks.